2011
DOI: 10.3390/polym3041944
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Particle Diameters in Miniemulsion Reversible-Deactivation Radical Polymerization

Abstract: Various types of controlled/living radical polymerizations, or using the IUPAC recommended term, reversible-deactivation radical polymerization (RDRP), conducted inside nano-sized reaction loci are considered in a unified manner, based on the polymerization rate expression,. Unique miniemulsion polymerization kinetics of RDRP are elucidated on the basis of the following two factors: (1) A high single molecule concentration in a nano-sized particle; and (2) a significant statistical concentration variation amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(58 citation statements)
references
References 30 publications
(82 reference statements)
2
55
0
1
Order By: Relevance
“…Figure 2 shows the calculated results based on the Monte Carlo (MC) simulation method proposed in [3,12], with k p = 500 L¨mol´1¨s´1. It is clearly shown that the polymerization rate increases significantly for d p < 250 nm, which shows excellent agreement with Equation (5).…”
Section: Conventional Free-radical Polymerizationsupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 2 shows the calculated results based on the Monte Carlo (MC) simulation method proposed in [3,12], with k p = 500 L¨mol´1¨s´1. It is clearly shown that the polymerization rate increases significantly for d p < 250 nm, which shows excellent agreement with Equation (5).…”
Section: Conventional Free-radical Polymerizationsupporting
confidence: 78%
“…I already discussed the threshold diameters in the earlier articles [4,5]. However, the statistical variation effect of the key component concentration among the particles was considered at the same time in these articles, which seems to make the discussion rather complicated.…”
Section: Introductionmentioning
confidence: 99%
“…By considering the high SMC effect for the radical concentration, or by using the relationship [R • ] = K [PXP]/[XP], the threshold particle diameter can also be represented by: Dp,normalR(1)=6n¯φAπNnormalA[normalR]bulk1/3 …”
Section: Theoreticalmentioning
confidence: 99%
“…When RDPRs are conducted in small polymerization loci, the strict RAFT polymerization rate expression is given by: Rnormalp=knormalpK[M]i [PXP]i[XP]i where the subscript, i shows the concentration in the i th droplet, and 〈 〉 represents the average over all i 's. Assuming a uniform droplet system, 〈 〉 reduces to a simple number average.…”
Section: Theoreticalmentioning
confidence: 99%
“…Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO). Tabela 1, estudos teóricos sobre a polimerização RAFT em miniemulsão também já foram publicados [90][91][92][93][94][95][96][97] , contribuindo com a melhor compreensão sobre a cinética de polimerização (e outras características) desse sistema.…”
Section: Polimerização Raft Em Miniemulsãounclassified